Prevalence Differences of Mental Disorders (Neurotic, Substance Use, Psychotic, and PTSD) Based on Gender in the Adult Population - Noki Irawan Saputra; Winda Ratna Wulan; Zesty Virgiandita; Hadi Rahmatsyah; Dedi Nurhasan Ashari; Andria Pragholapati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Mental disorders represent a significant global health concern, adversely affecting individuals' well-being and quality of life. Empirical evidence suggests gender-based differences in the prevalence of mental disorders, yet comprehensive analyses within adult populations remain limited. This study aimed to examine gender differences in the prevalence of four major categories of mental disorders—neurotic disorders, substance use disorders (SUD), psychotic disorders, and post-traumatic stress disorder (PTSD)—in the adult population. The study population consisted of adult patients aged 18 years and older who were present in the designated research area during the study period. From this population, a total sample of 2,875 respondents was targeted using a consecutive sampling technique, where every eligible individual was selected in sequence until the required sample size was achieved. Inclusion criteria included adults who were able to communicate and willing to complete the questionnaire, while those with severe cognitive impairment or in emergency conditions were excluded. Data were collected using the Self-Reporting Questionnaire (SRQ-29), a validated and reliable instrument comprising 29 closed-ended items that assess symptoms across four mental health domains: neurotic, substance use, psychotic, and PTSD. Each “YES” answer was scored as 1 and each “NO” as 0. The responses were analyzed using SPSS version 25.0. Descriptive statistics (frequencies and percentages) were used to summarize the data, while the Chi-Square Test of Independence was applied to examine gender-based differences. Additionally, Odds Ratios (OR) and 95% confidence intervals were calculated to assess the strength of association between gender and mental disorder indications. The findings revealed that neurotic disorders, psychotic disorders, and PTSD were more prevalent in females than in males. Neurotic disorders affected 47.7% of females and 28.3% of males; psychotic disorders were present in 32.6% of females and 27.2% of males; PTSD affected 63.6% of females compared to 46.8% of males. No cases of substance use disorders were reported in either gender group. There are significant gender differences in the prevalence of certain mental disorders, with females exhibiting higher rates of neurotic disorders, psychotic disorders, and PTSD. These findings highlight the need for gender-responsive approaches in mental health interventions, services, and public health policy planning.